The Transformation of Occupied Territory in International Law - Carcano, Andrea (Leiden Studies on the Frontiers of International Law, 2015)
Building on a broad historical foundation, this study offers a comprehensive treatment of the international law issues that have arisen in connection with, and as a result of, the 'transformative' occupation of Iraq and of their significance for the development of international law.